Effectiveness of Progressive Muscle Relaxation Therapy on Blood Pressure in Elderly Hypertension Sufferers - Arifin, Mohammad Fahrul; Fauziansyah, Ahmad; Nur Faizah, Hanim; Eliana, Dika Efa (Universitas Pahlawan Tuanku Tambusai, 2025)
Hypertension is a major global health concern linked to heart disease, stroke, and kidney failure, often worsened by inactivity, poor diet, and chronic stress. This study assessed changes in average blood pressure among elderly hypertensive patients before and after PMR therapy. This study applied a basic quantitative approach using a one-group pre-test and post-test design. Thirty elderly people with hypertension were chosen from the Elderly Social Services Home in Turusgede, Rembang, using purposive sampling. The intervention involved progressive muscle relaxation (PMR), which was done three times over one week, with each session lasting 10-15 minutes. Blood pressure was measured before and after the intervention using a sphygmomanometer. Data analysis was conducted using the Wilcoxon signed-rank test. The average age of participants was 66.30 ± 8.10 years, with a 95% confidence interval ranging from 63.27 to 69.33 years. Most of the participants were female, comprising 53.3% of the sample. Before the intervention, the average systolic blood pressure recorded was 143.33 mmHg, which decreased to a median value of 132.67 mmHg following the therapy. Statistical analysis confirmed a significant change between the pre- and post-intervention readings (p = 0.000; α < 0.05). PMR has been shown to effectively lower both systolic and diastolic blood pressure in older adults with hypertension. As a non-drug approach, it provides a straightforward, safe, and easily implementable technique that can be used regularly to aid in controlling blood pressure among the elderly.